Radiation catalytic ionization detoxification system and use thereof and radiation catalytic ionization detoxification method

By designing an irradiation catalytic ionization and detoxification system, using the gas-liquid mixing and reaction tube design, combined with the photocatalytic performance of FeWO4-rGO composite materials, the food safety risks and the lack of large-scale production equipment in the prior art are solved, and efficient water sterilization and edible oil detoxification effects are achieved.

CN116440830BActive Publication Date: 2025-03-11QINGDAO AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310432102.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2025-03-11
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

The prior art performs radiation catalytic ionization and detoxification under laboratory conditions, which poses food safety risks and lacks suitable equipment under large-scale production conditions to detoxify and sterilize liquid materials.

Method used

An irradiation catalytic ionization and detoxification system is designed, including a gas-liquid mixer and a reaction tube. The air carrying reactive oxygen is used to mix gas-liquid with the liquid to be detoxified, and the reactive oxygen is continuously supplemented through the U-shaped tube and the gas replenishment tube in the reaction tube. FeWO4-rGO composite material is used as the photocatalytic material.

Benefits of technology

It realizes efficient detoxification of water sterilization and edible oil removal of aflatoxins without direct liquid contact with photocatalytic materials, improving food safety and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116440830B_ABST
    Figure CN116440830B_ABST
Patent Text Reader

Abstract

The present invention discloses a radiation catalytic ionization detoxification system, including a gas-liquid mixer for mixing air carrying active oxygen after radiation catalytic ionization with liquid materials to be detoxified and a reaction tube for circulating the mixed gas-liquid mixture. The detoxification system of the present invention can be used for water sterilization or edible oil aflatoxin removal. The radiation catalytic ionization box in the system can provide the system with air containing active oxygen. The box body uses a mesh with photocatalytic material attached, which not only increases the content of photocatalytic material in a unit space, but also increases the area of ​​illumination because the photocatalytic material is evenly attached to the surface of the mesh. The system uses a U-shaped tube as a reaction tube, and the length of the reaction tube can be freely designed according to the actual detoxification requirements. The installation is convenient and quick. For the detoxification efficiency of the system, the system of the present invention uses an air supply pipe to continuously replenish new air carrying active oxygen after radiation catalytic ionization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of radiation catalytic ionization equipment, and in particular relates to a radiation catalytic ionization detoxification system and a use thereof, and a radiation catalytic ionization detoxification method. Background Art

[0002] The active oxygen after irradiation catalytic ionization is obtained through irradiation catalytic ionization technology. Radiant catalytic ionization (RCI) is an emerging sterilization and detoxification technology that can be used without restriction in environments with people, animals and plants because it does not produce potentially dangerous byproducts such as ozone, formaldehyde or carbon monoxide. The core of this technology is the photocatalytic effect, which is to generate electrons (e) by absorbing light energy with photocatalytic materials. – ) and holes (h + ) is converted into reactive oxygen species (ROS) with strong oxidizing ability, participating in the redox reaction of organic matter. In the existing technology, when this technology is used for detoxification and sterilization, it is carried out under laboratory conditions. During the experiment, the liquid needs to directly contact the photocatalytic material, which brings certain food safety risks. At the same time, there is currently no suitable equipment to complete the detoxification and sterilization of a large amount of liquid materials under production conditions.

[0003] Photocatalytic materials are crucial to radiation catalytic ionization technology. Different photocatalytic materials have different efficiencies in producing active oxygen. Currently, there are relatively few types of photocatalytic materials available. The more common materials are TiO 2 , ZnO, etc. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a radiation catalytic ionization detoxification system, including a gas-liquid mixer for mixing air carrying active oxygen after radiation catalytic ionization with a liquid material to be detoxified and a reaction tube for circulating the mixed gas-liquid mixture.

[0005] Based on the above scheme, the reaction tube includes several U-shaped tubes and connecting tubes for connecting the U-shaped tubes; the end of the straight tube section of the U-shaped tube is detachably connected to an air supply tube for filling the U-shaped tube with air carrying active oxygen after irradiation catalytic ionization; and several air supply holes are arranged on the wall of the air supply tube.

[0006] On the basis of the above solution, a plurality of fins are further provided on the air supply pipe.

[0007] On the basis of the above scheme, the air carrying active oxygen after radiation catalytic ionization is provided by a radiation catalytic ionization box; the radiation catalytic ionization box includes a box body, a plurality of mesh sheets arranged in the box body and a lamp tube for providing an irradiation light source; the mesh sheets are attached with a photocatalytic material that produces active oxygen after light irradiation.

[0008] Based on the above scheme, a fixing frame for fixing the mesh and the lamp tube is also provided in the box; the fixing frame is provided with fixing holes for fixing the lamp tube and fixing columns for fixing the mesh; the mesh is provided with mounting holes for the lamp tube to pass through and fixing holes for the fixing columns to pass through.

[0009] Based on the above scheme, the photocatalytic material is FeWO 4 -rGO composites.

[0010] The present invention also provides a method for preparing FeWO 4 -rGO composite material method, specifically, the method comprises the following steps:

[0011] (1) FeWO 4 Preparation

[0012] First, 5 mmol FeCl 3 6H 2 O and 5mmol Na 2 WO 4 ·2H 2 O were dissolved in 25 mL of distilled water. Then, FeCl 3 Ascorbic acid was added to the solution to completely dissolve it. 2 WO 4 The solution was slowly added to the above mixture. After further stirring for 30 min, the mixture was added to a 100 mL autoclave (the autoclave was only used as a reaction vessel) and kept at 150-200°C for more than 9 h. The autoclave was then cooled naturally to room temperature. The resulting precipitate was collected by centrifugation, washed several times with distilled water and anhydrous ethanol, and dried in air at 80°C for 6 h.

[0013] Among them: Fe 3+ : The molar ratio of ascorbic acid is: 5:0.2-5:1;

[0014] (2) FeWO 4 Preparation of rGO composites

[0015] First, 2g FeWO 4 Add 300 mL of ethanol and treat with ultrasound (ultrasound condition 300W) for 30 min. Add 2 mL of APTES to FeWO 4After the suspension was obtained, the mixture was heated at 70 °C for 4 h. Subsequently, the powder was collected, washed with ethanol several times, and then dried at 80 °C overnight. 4 60 mL of distilled water was added and ultrasonicated (ultrasonication condition 300 W) for 15 min, and then 0.05 g of rGO was added. After stirring for 60 min, the resulting suspension was transferred to an autoclave and kept at 180 °C for 12 h. The resulting product was collected, washed with water and dried at 80 °C overnight to obtain FeWO 4 -rGO.

[0016] The above-mentioned irradiation catalytic ionization detoxification system can be used for water sterilization or edible oil aflatoxin removal.

[0017] The present invention also provides a radiation catalytic ionization detoxification method, which uses the above-mentioned system and includes the steps of obtaining active oxygen by radiation catalytic ionization, mixing air carrying active oxygen after radiation catalytic ionization with liquid material to be detoxified, and detoxifying bacteria or aflatoxins in the liquid material with active oxygen.

[0018] The detoxification system of the present invention can be used for sterilizing water or removing aflatoxin from edible oil. The irradiation catalytic ionization box in the system can provide the system with air containing active oxygen. A mesh sheet with a photocatalytic material attached thereto is used in the box, which not only increases the content of the photocatalytic material in the unit space, but also increases the area of ​​illumination because the photocatalytic material is evenly attached to the surface of the mesh sheet. The system uses a U-shaped tube as a reaction tube, and the length of the reaction tube can be freely designed according to the actual detoxification requirements. The installation is convenient and quick. For the detoxification efficiency of the system, the system of the present invention uses an air supply pipe to continuously replenish new air carrying active oxygen after irradiation catalytic ionization. At the same time, the photocatalytic material used in the present invention - FeWO 4 -rGO composite material, the preparation method of the material is simple, and ascorbic acid used in the method can not only be used as a reducing agent, but also as a structure-directing agent to synthesize FeWO 4 The surface charge of the product was modified to construct FeWO with sufficient interfacial contact via electrostatic self-assembly. 4 -rGO nanocomposite photocatalyst provides a reasonable method. FeWO prepared by the method of the present invention 4 -rGO composites have strong photocatalytic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the principle of the system described in Example 1;

[0020] Figure 2 It is a schematic diagram of the structure of the irradiation catalytic ionization box in the detoxification system of the present invention;

[0021] Figure 3 It is a schematic diagram of the structure of the mesh in the detoxification system of the present invention;

[0022] Figure 4 It is a schematic diagram of the structure of the reaction tube in the detoxification system of the present invention;

[0023] Figure 5 It is a structural schematic diagram and a partial enlarged schematic diagram of the air supply pipe in the detoxification system of the present invention;

[0024] Figure 6 It is a schematic diagram of the structure of the fixing frame in the detoxification system of the present invention;

[0025] Figure 7 The XRD patterns of the samples in Example 2, where (a) snowflake-shaped FeWO 4 (b)FeWO 4 -rGO-U and (c)FeWO 4 -rGO;

[0026] Figure 8 Raman spectra of the samples in Example 2, where (a) GO, (b) FeWO 4 and (c) FeWO 4 -rGO.

[0027] Fig. 9 is the UV-vis diffuse reflectance spectrum of the sample in Example 2, where (a) FeWO 4 (b)FeWO 4 -rGO-U and (c)FeWO 4 -rGO;

[0028] Fig.10 is the N of the sample in Example 2 2 Adsorption and desorption isotherms; (a) snowflake-shaped FeWO 4 , (b) FeWO 4 -rGO-U and (c)FeWO 4 -rGO;

[0029] Fig.11 The scanning electron microscope and transmission electron microscope images of the sample in Example 2; (a, b) snowflake-shaped FeWO 4 , (c) FeWO 4 SEM images of FeWO-rGO composites. (d) (e) HRTEM and (f) 4 -Corresponding SAED of rGO composites;

[0030] Fig.12 FeWO under visible light irradiation 4-Schematic reaction mechanism diagram of the photocatalytic redox reaction on the rGO composite photocatalyst;

[0031] Fig.13 FeWO generated under different temperature conditions 4 SEM images of (a) 120℃, (b) 150℃, (c, d) 200℃;

[0032] Fig.14 FeWO generated under different time conditions 4 SEM images and XRD patterns of the prepared samples after hydrothermal treatment at 180℃ for different reaction times.

[0033] Fig.15 Schematic diagram of the oxidation process of L-ascorbic acid;

[0034] Fig.16 FeWO with snowflake structure 4 Schematic diagram of the formation of

[0035] Fig.17 FeWO generated under different ascorbic acid dosage conditions 4 SEM image of Fe 3+ : The molar ratio of ascorbic acid is different, including (a, b) 5:0.2, (c, d) 5:0.3 and (e, f) 5:1;

[0036] Fig.18 FeWO prepared from different raw materials 4 SEM images of (a, b) Fe(NO 3 ) 3 Replace FeCl 3 ; (c, d) 5mmol FeCl 3 6H 2 O, 5mmol Na 2 WO 4 ·2H 2 O, 0.5 mmol ascorbic acid and 0.1 mmol hexadecyltrimethylammonium bromide. DETAILED DESCRIPTION

[0037] The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art.

[0038] The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention in any way.

[0039] Example 1

[0040] like Figure 1 As shown, the present patent provides a radiation catalytic ionization detoxification system, which includes a gas-liquid mixer 1 for mixing air carrying active oxygen after radiation catalytic ionization with a liquid material to be detoxified and a reaction tube 4 for circulating the mixed gas-liquid mixture.

[0041] The active oxygen after irradiation catalytic ionization is obtained through irradiation catalytic ionization technology. Radiant catalytic ionization (RCI) is an emerging sterilization and detoxification technology that can be used without restriction in environments with people, animals and plants because it does not produce potentially dangerous byproducts such as ozone, formaldehyde or carbon monoxide. The core of this technology is the photocatalytic effect, which is to generate electrons (e) by absorbing light energy with photocatalytic materials. – ) and holes (h + ) is converted into reactive oxygen species (ROS) with strong oxidizing ability, participating in the redox reaction of organic matter. There are many photocatalytic materials available, for example: photocatalytic materials can use gC 3 N 4 and / or FeWO 4 -rGO composites, TiO 2 、Bi 2 WO 6 ,Upconversion nanoparticles@TiO 2 、Ag-AgCl / α-Fe 2 O 3 wait.

[0042] The gas-liquid mixer 1 is a device for fully mixing gas and liquid. During the mixing process, the gas in the liquid is broken into small bubbles or micron or nanometer bubbles, thereby increasing the contact area between the gas and the liquid, and effectively improving the redox reaction between the active oxygen in the gas and the object to be treated in the liquid.

[0043] The liquid material to be detoxified can be edible oil contaminated with aflatoxin (it can also be zearalenone, vomitoxin, etc.), beverages, soy milk, milk, etc., or it can be sewage to be sterilized.

[0044] The detoxification system of the present invention performs detoxification in a manner that the photocatalytic material does not contact the liquid to be treated. Firstly, secondary contamination of the liquid by the photocatalytic material can be avoided. Secondly, the risk of quality reduction caused by direct exposure of the liquid to light can be avoided (for example, light can change the acid value, peroxide value, unsaturated fatty acids, etc. of peanut oil).

[0045] During the circulation of the air carrying active oxygen and the liquid material to be detoxified in the reaction tube 4, the active oxygen continuously performs redox reaction, but with the continuous consumption of active oxygen in the air, the oxidizing capacity of the gas gradually decreases. In order to solve this problem, it is necessary to continuously fill the air carrying active oxygen ionized by irradiation catalysis in the process of the gas-liquid mixture circulating in the reaction tube 4, so as to achieve the effect of rapid treatment. When the amount of active oxygen in the active oxygen-containing air filled into the liquid material is sufficient, there is no need to add new active oxygen into the reaction tube 4. However, if the active oxygen-containing air filled into the liquid material is not enough to treat the liquid material to be detoxified, based on the above technical solution, it is necessary to continuously fill the air carrying active oxygen ionized by irradiation catalysis in the process of the gas-liquid mixture circulating in the reaction tube 4.

[0046] As a specific embodiment, the present invention provides a specific implementation example of a reaction tube 4, such as Figure 4 As shown, the reaction tube 4 includes a plurality of U-shaped tubes 4-1 and connecting tubes 4-2 for connecting the U-shaped tubes 4-1; the connecting tubes 4-2 can be connected between the U-shaped tubes 4-1 by threaded connection. This method can freely design the length of the reaction tube according to the actual detoxification requirements, and the installation is convenient and quick.

[0047] During the circulation of the mixed material in the reaction tube 4, the active oxygen in the air is continuously consumed, and the oxidizing capacity of the gas is gradually reduced. Therefore, in order to improve the detoxification efficiency, it is necessary to maintain the content of active oxygen in the mixed material. For this purpose, it is necessary to continuously replenish new air carrying active oxygen after irradiation catalytic ionization. As a specific implementation scheme, Figure 4 As shown, the end of the straight tube section of the U-shaped tube 4-1 is designed as an open structure that can be opened or closed at any time. When the active oxygen gas needs to be supplemented, the opening is opened, and the air supply pipe 4-3 is inserted into the straight tube section from the opening, and the air carrying active oxygen after ionization by radiation catalysis is filled into the U-shaped tube 4-1 by the air supply pipe 4-3; the air supply pipe 4-3 is detachably connected to the end of the straight tube section of the U-shaped tube 4-1; when air supply is not needed, the end of the straight tube section of the U-shaped tube 4-1 can be sealed with an end plug (not shown in the figure). A plurality of air supply holes 4-31 are arranged on the wall of the air supply pipe 4-3.

[0048] In order to improve the mixing degree between the newly added gas and liquid, Figure 5 As shown, a plurality of fins 4-32 are arranged on the gas supply pipe 4-3. The arrangement of the plurality of fins 4-32 can not only break the newly supplied gas into small bubbles, but also effectively improve the mixing degree of gas and liquid.

[0049] For the detoxification system of the present invention, the amount of active oxygen carried in the air is crucial to the detoxification effect. In order to increase the concentration of active oxygen carried in the air, the present invention provides a specific implementation case, such as Figure 2 As shown, the air carrying active oxygen after radiation catalytic ionization is provided by a radiation catalytic ionization box 2; the radiation catalytic ionization box 2 includes a box body 2-1, a plurality of mesh sheets 2-2 arranged in the box body 2-1 and a lamp tube 2-3 for providing an irradiation light source; the mesh sheets 2-2 are attached with photocatalytic materials that generate active oxygen after light irradiation.

[0050] The several mesh sheets 2-2 with photocatalytic materials attached thereto provided in the irradiation catalytic ionization box 2 of the present invention can stimulate more active oxygen under the irradiation of the lamp tube 2-3. The box body 2-1 is open at both ends, one end for air intake and the other end for air outlet. The active oxygen is driven by a fan (not shown in the figure) from the irradiation catalytic ionization box 2 to enter the gas-liquid mixer 1 to mix with the liquid material to be treated. Specifically, the mesh sheet 2-2 can be a mesh sheet of light-transmitting material, and the surface of the mesh sheet 2-2 is attached with photocatalytic materials. Compared with the existing catalytic ionization equipment, the irradiation catalytic ionization box 2 of the present invention uses a mesh sheet 2-2 with photocatalytic materials attached thereto, instead of arranging the photocatalytic materials on a flat plate, which not only increases the content of the photocatalytic materials in the unit space, but also increases the area of ​​illumination because the photocatalytic materials are evenly attached to the surface of the mesh sheet. At the same time, the mesh structure of the mesh 2-2 not only meets the need for gas circulation, but also facilitates the circulating air to pass through the mesh and take away the active oxygen generated by the photocatalytic material on the mesh under the premise of irradiation, and more photocatalytic materials are loaded, thereby providing sufficient active oxygen for the system. As a specific implementation case, the mesh 2-2 uses a light-transmitting acrylic plate, PC or PVC hard plate with air holes, on which the photocatalytic material is attached.

[0051] As a specific application scenario, Figure 2 As shown, the box body 2-1 is also provided with a fixing frame 2-4 for fixing the mesh 2-2 and the lamp tube 2-3; the fixing frame 2-4 is provided with a fixing hole 2-41 for fixing the lamp tube 2-3 and a fixing column 2-42 for fixing the mesh 2-2; Figure 3 As shown, the mesh 2-2 is provided with a mounting hole 2-21 for the lamp tube 2-3 to pass through and a fixing hole 2-22 for the fixing column 2-42 to pass through. In this way, the mesh 2-2, the lamp tube 2-3 and the fixing frame 2-4 can be assembled in advance outside the box 2-1, and then inserted into the box 2-1 after assembly, and the fixing frame 2-4 is fixed in the box 2-1 (the four legs of the fixing frame 2-4 are fixed to the inner wall of the box 2-1). Figure 3Only one implementation method of the position and number of the mounting hole 2-21 and the fixing hole 2-22 is given. When in use, the position and number of the mounting hole 2-21 and the fixing hole 2-22 can be freely set as needed.

[0052] The structure of the fixing frame 2-4 is as follows Figure 6 As shown, because the box 2-1 is ventilated when in use, in order to increase the stability of the mesh 2-2 and the lamp tube 2-3, as shown in FIG. Figure 2 As shown, a fixing frame is added on the other side of the mesh (the left side in the figure), and a round hole in the middle of the fixing frame replaces the fixing column. The round hole is used for inserting the fixing column 2-42, which will not be described here.

[0053] The specific type of lamp tube 2-3 is not particularly limited, as long as it can irradiate the catalytic semiconductor material to produce active oxygen, such as an ordinary fluorescent lamp tube or a lamp tube that produces light of a special wavelength, such as a 300-watt xenon lamp and an optical cutoff filter used in Example 3.

[0054] When in use, turn on the lamp tubes 2-3 in the irradiation catalytic ionization box 2 for irradiation catalysis, use a pump to pump the material to be treated in the liquid tank 3 into the gas-liquid mixer 1, and at the same time, use a fan to fill the active oxygen generated by the irradiation catalytic ionization box 2 into the gas-liquid mixer 1 to mix with the liquid material, and the mixed material is pumped into the reaction tube 4 by the pump for detoxification. In the reaction tube 4, the oxidizing capacity of the gas gradually decreases. Therefore, in order to improve the detoxification efficiency, the gas supply pipe 4-3 is used to supply gas to the reaction tube 4.

[0055] Example 2

[0056] Based on the detoxification system in Example 1, this example provides a photocatalytic material - FeWO that can be used in the system 4 -rGO composites, the FeWO 4 -rGO composites were prepared by the following method:

[0057] (1) FeWO 4 Preparation

[0058] First, 5 mmol FeCl 3 6H 2 O and 5mmol Na 2 WO 4 ·2H 2 O were dissolved in 25 mL of distilled water. Then, FeCl 3 0.5 mmol ascorbic acid was added to the solution to completely dissolve it. 2 WO 4The solution was slowly added to the above mixture. After further stirring for 30 min, the mixture was added to a 100 mL autoclave (the autoclave in this example was only used as a reaction vessel) and kept at 180°C for 12 h. The autoclave was then cooled naturally to room temperature. The resulting precipitate was collected by centrifugation, washed several times with distilled water and anhydrous ethanol, and dried in air at 80°C for 6 h.

[0059] (2) FeWO 4 Preparation of rGO composites

[0060] First, 2g FeWO 4 Add 300 mL of ethanol and treat with ultrasound (ultrasound condition 300W) for 30 min. Add 2 mL of APTES to FeWO 4 After the suspension was obtained, the mixture was heated at 70 °C for 4 h. Subsequently, the powder was collected, washed with ethanol several times, and then dried at 80 °C overnight. 4 60 mL of distilled water was added and ultrasonicated (ultrasonication condition 300 W) for 15 min, and then 0.05 g of rGO was added. After stirring for 60 min, the resulting suspension was transferred to an autoclave and kept at 180 °C for 12 h. The resulting product was collected, washed with water and dried at 80 °C overnight to obtain FeWO 4 -rGO.

[0061] Example 3

[0062] In order to compare the superiority of the charge modification method, the snowflake-shaped FeWO prepared in step (1) was subjected to 4 、FeWO 4 -rGO-U(FeWO 4 -rGO-U is a direct conversion of FeWO 4 The mixture after grinding and mixing with rGO) and FeWO prepared by the above method 4 -rGO for comparative testing.

[0063] (1) XRD test

[0064] The results are as follows Figure 7 All product diffraction peaks can be attributed to FeWO 4 In addition, no diffraction peak of rGO was observed.

[0065] (2) Raman spectroscopy test

[0066] The results are as follows Figure 8 As shown in Figure 2, Raman analysis further confirmed that the composite contained rGO. Figure 8As shown in (a), at 1596 and 1346 cm -1 Two main peaks were observed near , which should be attributed to the G band and D band of GO. Figure 8 As shown in (b), 93, 132, 215, 179, 349, 683 and 875 cm -1 The peak at corresponds to FeWO 4 Raman spectrum of FeWO 4 -rGO composites, in addition to the FeWO 4 In addition to the peaks of rGO, the G band and D band of rGO are located at 1598 and 1345 cm -1 This clearly shows that the prepared rGO-FeWO 4 rGO exists in the composite material.

[0067] (3) UV-vis diffuse reflection

[0068] The results are as follows Fig. 9 As shown, the optical properties of the material can be characterized by UV-vis DRS spectroscopy, snowflake-shaped FeWO 4 It shows strong absorption in the visible light region. By adding rGO, it can be clearly observed that the absorption of visible light in the region between 500 and 800 nm is enhanced. The expansion of the light absorption range can achieve more efficient use of the solar spectrum and enhanced photocatalytic activity. In addition, FeWO 4 The background absorption of the -rGO composite material in the visible light region is significantly enhanced.

[0069] (4) N 2 Adsorption and desorption

[0070] N of the prepared product 2 Adsorption-desorption isotherms are shown in Fig.10 FeWO 4 -rGO、FeWO 4 -rGO-U and pure snowflake-like FeWO 4 The specific surface areas of 3 g -1 , there is no significant difference in the values.

[0071] (5) SEM and TEM testing

[0072] The results are as follows Fig.11 As shown, the snowflake-like FeWO was studied by SEM and TEM. 4 and FeWO 4 -rGO composite material morphology and structure. Fig.11 As shown in (a), FeWO 4It is composed of uniform snowflake-shaped crystallites with a diameter of about 1µm. High-magnification SEM shows that each snowflake-shaped FeWO has approximately six-fold symmetry. 4 It is composed of nanorods assembled in a specific direction ( Fig.11 b). As for FeWO 4 -rGO composites ( Fig.11 medium cd), FeWO 4 was wrapped by rGO nanosheets, which means that FeWO 4 There is a possibility of sufficient contact and effective interfacial interaction between FeWO and rGO. 4 TEM images of the -rGO composites Fig.11 As shown in (d). FeWO 4 The components were deposited on the surface of rGO sheets. The samples showed some wrinkles at the edges of both rGO sheets and interlayer sheets, providing more active sites for adsorption. Fig.11 (e) shows clear lattice fringes with a spacing of 0.22 nm, which corresponds to FeWO 4 In addition, selected area electron diffraction (SAED) showed well-defined rings, which confirmed the polycrystalline nature of the sample.

[0073] like Fig.12 As shown in Figure 2, under visible light irradiation, electrons in the valence band (VB) are excited to the conduction band (CB), leaving holes in the VB and forming holes in the FeWO 4 Then, the photogenerated electrons (e-) are transferred from FeWO 4 The microstructures were transferred onto rGO sheets and further reacted with O 2 The reaction produces highly reactive free radicals (O 2 ·−). FeWO 4 The holes in the VB react with water to form active OH•. These free radicals can attack fungal toxins and eliminate them through photocatalytic redox reactions. 4 Compared with the GO-U composite, the surface charge modification was to construct FeWO with sufficient interfacial contact via electrostatic self-assembly. 4 -rGO nanocomposite photocatalysts provide a reasonable approach. All the above factors contribute to the improvement of the separation efficiency of electron-hole pairs, thus significantly improving the FeWO 4 - Photoactivity of rGO composites.

[0074] FeWO generated under different temperature conditions 4 Morphological changes

[0075] First, 5 mmol FeCl 3 6H 2 O and 5mmol Na2 WO 4 ·2H 2 O were dissolved in 25 mL of distilled water. Then, FeCl 3 0.5 mmol ascorbic acid was added to the solution to completely dissolve it. 2 WO 4 The solution was slowly added to the above mixture. After further stirring for 30 min, the mixture was added to a 100 mL autoclave and kept at a certain temperature for 12 h. The autoclave was then cooled naturally to room temperature. The resulting precipitate was collected by centrifugation, washed several times with distilled water and anhydrous ethanol, and dried in air at 80 °C for 6 h.

[0076] The results are as follows Fig.13 As shown, Fig.13 It shows that the temperature has an influence on FeWO 4 The influence of sample morphology. Irregular shapes were observed at 120 °C ( Fig.13 When the temperature is increased to 150℃, although the morphology of the product is similar to that of the sample hydrothermally treated at 120℃, the average size of the product is smaller. When the temperature is increased to 180℃ ( Fig.11 In (a) and (b), the prepared samples consist of snowflakes with perfect uniformity. When the temperature is 200°C, although the sample maintains the snowflake-like structure, the surface of the nanorods becomes smoother ( Fig.13 (c) and (d)). This result also shows that the final morphology depends on the FeWO 4 The temperature at which crystals form.

[0077] FeWO generated under different time conditions 4 Morphological changes

[0078] First, 5 mmol FeCl 3 6H 2 O and 5mmol Na 2 WO 4 ·2H 2 O were dissolved in 25 mL of distilled water. Then, FeCl 3 0.5 mmol ascorbic acid was added to the solution to completely dissolve it. 2 WO 4 The solution was slowly added to the above mixture. After further stirring for 30 min, the mixture was added to a 100 mL autoclave and kept at 180 °C for a certain period of time. The autoclave was then cooled naturally to room temperature. The resulting precipitate was collected by centrifugation, washed several times with distilled water and anhydrous ethanol, and dried in air at 80 °C for 6 h.

[0079] To understand the snowflake-like FeWO 4 Growth mechanism of the materials prepared at different hydrothermal times. Fig.14 When the reaction time is less than 2 h, the product is composed of large oval particles ( Fig.14 (a) and (b)). Fig.14 (c) shows an image of the sample after 6 h of reaction, indicating the formation of plate-like aggregates. These aggregates are formed by many nanoparticles and nanorods. As the process continues, snowflake-like FeWO appears after 9 h. 4 structure, showing hexagonal symmetry ( Fig.14 (d)). It should be noted that the nanorods extend outward from the center of the aggregate in a self-assembled form. As the reaction continues, the irregular particles disappear and longer nanorods are formed, indicating that longer nanorods grow at the expense of smaller particles. After 12 h, FeWO 4 Nanoparticles on the snowflake surface grow along their axis to form nanorods ( Fig.14 (e). These images clearly demonstrate the shape evolution of the obtained products from nanoparticle-built aggregates to snowflake-like structures. Fig.14 (f) shows FeWO prepared at different hydrothermal times. 4 XRD patterns of the samples. The crystalline phase is enhanced with increasing hydrothermal time. All XRD patterns can be easily identified as FeWO 4 .

[0080] Based on the above analysis, the shape evolution process of the snowflake-like microstructure is as follows Fig.15 and 16 In this process, the oxygen-containing groups in DHA and DGA (such as -OH and C=O) strongly prefer to react with Fe 2+ The cations coordinate and form a complex. Therefore, the free Fe 2+ The concentration of cations decreases. 4 The slow formation rate of WO will lead to the separation of nucleation and growth steps. 4 2- React with the complex to form FeWO 4 The DHA and DGA in the reaction system are reacted with FeWO 4 At the same time, due to the reduction of the surface energy of the crystal core and the hydrogen interaction between DHA and DGA, FeWO 4 The crystal nuclei tend to aggregate. In addition, due to the 4Due to the high intrinsic anisotropy of FeWO, the nanoparticles prefer to grow into nanorods through directional attachment. As the hydrothermal treatment time increases, a snowflake-like microstructure is formed. We can conclude that the formation of the hierarchical snowflake-like microstructure is the result of ascorbic acid-induced reduction, formation, and aggregation of nanoparticles, followed by the growth of nanorods and their subsequent self-assembly. According to the reported literature, after FeWO is modified with APTES, 4 With amine functional groups. Under the action of electrostatic attraction, FeWO 4 Anchored on the negatively charged surface of rGO nanosheets.

[0081] Effect of different amounts of ascorbic acid on product morphology

[0082] First, 5 mmol FeCl 3 6H 2 O and 5mmol Na 2 WO 4 ·2H 2 O were dissolved in 25 mL of distilled water. Then, FeCl 3 A certain amount of ascorbic acid was added to the solution to completely dissolve it. 2 WO 4 The solution was slowly added to the above mixture. After further stirring for 30 min, the mixture was added to a 100 mL autoclave and kept at 180 °C for 12 h. The autoclave was then cooled naturally to room temperature. The resulting precipitate was collected by centrifugation, washed several times with distilled water and anhydrous ethanol, and dried in air at 80 °C for 6 h.

[0083] The effects of different amounts of ascorbic acid on the product morphology were studied. Fig.17 shown. Fig.17 SEM images of samples prepared in the presence of different amounts of ascorbic acid (0.2 to 1 mmol) in the reaction system are shown. When 0.2 mmol ascorbic acid was added, disordered tiny particles were the main product (Figure 17 (a) (b)). After increasing the amount of ascorbic acid (0.3 mmol), some particle aggregates were formed ( Fig.17 Further increasing the amount of ascorbic acid to 0.5 mmol, the prepared sample consisted of snowflakes with perfect homogeneity and monodispersity ( Fig.11 (a) (b)). When the amount of ascorbic acid is as high as 1 mmol, the product is spherical and composed of nanorods ( Fig.17 Therefore, the new FeWO 4 The successful preparation of the nanostructures indicates that in this system, ascorbic acid can be used not only as a reducing agent but also as a structure-directing agent to synthesize FeWO 4product.

[0084] Effect of different raw materials on FeWO 4 Impact

[0085] In the case where step (1) in Example 2 remains unchanged, A only replaces FeCl 3 6H 2 O was replaced by an equimolar amount of Fe(NO 3 ) 3 9H 2 O and B only added 0.1 mmol of hexadecyltrimethylammonium bromide at the same time as the ascorbic acid was added.

[0086] The results are as follows Fig.18 As shown, FeWO 4 The morphology and size of the product depend on the iron precursor salt used. The anion of the iron precursor salt determines the FeWO 4 Under similar conditions, only Fe(NO 3 ) 3 Replace FeCl 3 , it is impossible to obtain a uniform snowflake-like structure assembled by nanorods. The corresponding SEM Fig.18 In addition to the iron precursor salt, we found that the presence of CTAB also affects the morphology of the final product, such as Fig.18 (c) (d) In the presence of CTAB, the final product can also be composed of nanorods, but the snowflake-like organized structure is not present at all. Therefore, CTAB can also provide additional control over the product morphology.

[0087] Aflatoxin (AFB 1 ) Degradation test, the steps are as follows:

[0088] 500 mg of flower-shaped FeWO prepared in Example 2 4 -rGO composites were coated on a glass substrate and then added to 100 mL of AFB 1 The suspension was stirred at 500 rpm in corn oil (concentration 16.8 ppb). Then it was stirred in the dark for 30 min to reach adsorption-desorption equilibrium. The suspension was irradiated with a 300-watt xenon lamp. 5 mL corn oil was collected at 0 min, 15 min, 30 min, 45 min, 60 min, and 75 min irradiation time. The concentration of AFB1 in peanut oil was tested by liquid chromatography, and the results are shown in Table 1. The control group was the snowflake FeWO prepared in the comparative example. 4 and FeWO 4 -rGO-U.

[0089] Table 1

[0090] Light exposure time (min) 0 15 30 45 60 75 Snowflake FeWO4 group AFB1 concentration (ppb) 16.8 15.3 14.2 13.6 12.8 13.8 AFB1 concentration of snowflake FeWO4-rGO-U group (ppb) 16.8 14.6 11.2 9.6 8.7 6.2 AFB1 concentration of snowflake FeWO4-rGO group (ppb) 16.8 12.1 9.6 4.1 3.6 2.5

[0091] It can be seen from Table 1 that compared with snowflake FeWO 4 and FeWO 4 Compared with rGO-U, flower-like FeWO 4 -rGO has excellent photocatalytic degradation performance for corn oil AFB1.

[0092] Application Example 2

[0093] The E. coli bacterial suspension was mixed with the prepared material, and an optical cutoff filter (λ>420nm) was used to irradiate with a 300-watt xenon lamp for antibacterial performance evaluation experiment. The bacterial suspension with different irradiation time intervals (0min, 5min, 10min, 15min, 20min, 25min) was spread on the LB agar plate, cultured in a 37℃ incubator for 4h, and the colony growth was observed. At the same time, the bacterial suspension was diluted, the plate count was performed, the number of surviving bacteria was determined, and the bactericidal efficiency was calculated.

[0094] Sterilization efficiency (%) = (N 0 -N t ) / N 0 ×100%

[0095] Note: N in the formula 0 and N t The number of colonies counted on the control group and sample plates

[0096] The test results are shown in Table 2.

[0097] Table 2

[0098] Light exposure time (min) 0 5 10 15 20 25 Sterilization efficiency of snowflake FeWO4 group 1 0.91 0.83 0.79 0.75 0.71 Bactericidal efficiency of snowflake-shaped FeWO4-rGO-U group 1 0.84 0.71 0.63 0.59 0.52 Bactericidal efficiency of snowflake-shaped FeWO4-rGO group 1 0.65 0.42 0.36 0.21 0.08

[0099] It can be seen from Table 2 that compared with snowflake FeWO 4 and FeWO 4 Compared with rGO-U, the snowflake-shaped FeWO prepared in this application 4 -rGO has excellent photocatalytic killing performance against Escherichia coli.

[0100] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A radiation catalytic ionization detoxification system, characterized in that: It comprises a gas-liquid mixer (1) for mixing air carrying active oxygen after catalytic ionization by radiation with a liquid material to be detoxified, and a reaction tube (4) for circulating the mixed gas-liquid mixture; The reaction tube (4) comprises a plurality of U-shaped tubes (4-1) and connecting tubes (4-2) for connecting the U-shaped tubes (4-1); the end of the straight tube section of the U-shaped tube (4-1) is detachably connected to an air supply tube (4-3) for filling the U-shaped tube (4-1) with air carrying active oxygen after ionization by radiation catalysis; and a plurality of air supply holes (4-31) are arranged on the wall of the air supply tube (4-3); The air supply pipe (4-3) is also provided with a plurality of fins (4-32); The air carrying active oxygen after irradiation catalytic ionization is provided by an irradiation catalytic ionization box (2); the irradiation catalytic ionization box (2) comprises a box body (2-1), a plurality of mesh sheets (2-2) arranged in the box body (2-1), and a lamp tube (2-3) for providing an irradiation light source; a photocatalytic material that generates active oxygen after light irradiation is attached to the mesh sheets (2-2); A fixing frame (2-4) for fixing the mesh (2-2) and the light tube (2-3) is also provided in the box body (2-1); a fixing hole (2-41) for fixing the light tube (2-3) and a fixing column (2-42) for fixing the mesh (2-2) are provided on the fixing frame (2-4); a mounting hole (2-21) for the light tube (2-3) to pass through and a fixing hole (2-22) for the fixing column (2-42) to pass through are provided on the mesh (2-2); The photocatalytic material is a FeWO4-rGO composite material.

2. The radiation catalytic ionization detoxification system according to claim 1, characterized in that: The FeWO4-rGO composite material is prepared by the following method: FeWO4 was added to ethanol and ultrasonicated; after APTES was added to the FeWO4 suspension, the mixture was heated at 70 °C for 4 h; Subsequently, the powder was collected, washed with ethanol, and dried; Afterwards, APTES-modified FeWO4 was added to distilled water and ultrasonicated, and then rGO was added; after stirring for 60 min, the resulting suspension was kept at 180 °C for 12 h; finally, the resulting product was collected, washed with water and dried at 80 °C to obtain FeWO4-rGO.

3. The radiation catalytic ionization detoxification system according to claim 2, characterized in that: The FeWO4 is prepared by the following method: First, FeCl3·6H2O and Na2WO4·2H2O are dissolved in distilled water respectively; then, ascorbic acid is added to the FeCl3 solution under continuous stirring to completely dissolve; then, the Na2WO4 solution is slowly added to the above mixture; after further stirring, the mixture is kept at high temperature for a period of time; then naturally cooled to room temperature; the resulting precipitate is collected by centrifugation, washed and dried.

4. Use of the irradiation catalytic ionization detoxification system according to any one of claims 1 to 3 in water sterilization or edible oil aflatoxin removal.

5. A radiation catalytic ionization detoxification method, characterized in that: The system according to any one of claims 1 to 3 comprises the steps of obtaining active oxygen by radiation catalytic ionization, mixing air carrying active oxygen after radiation catalytic ionization with liquid material to be detoxified, and detoxifying bacteria or aflatoxins in the liquid material by using active oxygen.

Citation Information

Patent Citations

  • Cylindrical solenoid type continuous flow-photocatalytic oxidation degradation water treatment device, system and method

    CN114772678A